POTENTIAL FEED RESOURCES FOR SWAMP BUFFALOES (Bubalus bubalis) RAISED UNDER OIL-PALM ECOSYSTEM - Zahari, M. Wan; Alimon, A. R.; Shanmugavelu, S. (Proceeding Buffalo International Conference, 2013)
The domesticated buffalo (Bubalus bubalis) in Malaysia is represented mostly by the swamp type. The total population of the animal is less than 130,000 heads with 59% in Peninsular Malaysia, 35% in Sabah and 6% in Sarawak.Â Rearing of swamp buffaloes under the plantation environment, both under grazing and pen-fed situations are of potential for meat production. The availability of grasses, legumes, shrubs and tree fodders under the plantation environment offer tremendous opportunities as feed resources for these animals. Palm kernel cake (PKC), oil palm fronds (OPF), palm press fibre (PPF), oil palm trunk (OPT), and palm oil mill effluent (POME) are potential feedstuffs to be utilized for in situ feeding of swamp buffaloes.Â Supplementation of high protein fodder leaves, such as Gliricidia sepium, Leucaena leucocephala, Morris alba and Asystasia intrusa could further enhance protein nutrition, especially for intensively-fed swamp buffaloes. Nutrient supplementation through non-medicated (UMMB) and medicated urea-molasses mineral blocks (MUMB) can also be considered to improve performances.Â Feeding strategies and examples of formulated ration for swamp buffalo meat production under oil palm plantation are highlighted